2000
DOI: 10.1007/s002449910038
|View full text |Cite
|
Sign up to set email alerts
|

Factors Controlling the Bioaccumulation of Mercury, Methylmercury, Arsenic, Selenium, and Cadmium by Freshwater Invertebrates and Fish

Abstract: Concentrations of mercury (Hg), methylmercury (MMHg), arsenic (As), selenium (Se), and cadmium (Cd) were measured in atmospheric deposition, stream water, and biota in two streams in western Maryland. Overall, concentrations were slightly higher in the water of the lower pH Herrington Creek tributary (HRCT). Bioaccumulation factors were also higher for HRCT compared to Blacklick Run (BLK). MMHg concentrations in biota increased with trophic level and essentially all the Hg was as MMHg in predatory insects and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
196
1
14

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(239 citation statements)
references
References 26 publications
28
196
1
14
Order By: Relevance
“…In the present article, we discussed this aspect by some previous data and the results were incorporated with our proposed hypothesis. Mason et al (2000) reported a decrease of arsenic levels with the increase of higher trophic level. He also suggested that the subsequent transfer of arsenic to higher trophic levels is related to both the ability of the organisms to depurate and the mode of accumulation, either directly from water or from foodstuffs.…”
Section: Arsenic Transfer Through Food Chainmentioning
confidence: 98%
“…In the present article, we discussed this aspect by some previous data and the results were incorporated with our proposed hypothesis. Mason et al (2000) reported a decrease of arsenic levels with the increase of higher trophic level. He also suggested that the subsequent transfer of arsenic to higher trophic levels is related to both the ability of the organisms to depurate and the mode of accumulation, either directly from water or from foodstuffs.…”
Section: Arsenic Transfer Through Food Chainmentioning
confidence: 98%
“…31 Entretanto, com o aumento do tamanho corporal dos organismos aquáticos, no caso dos peixes, verifica-se que há uma diminuição na contribuição do mercúrio dissolvido na água e, consequentemente, a transferência trófica torna-se o meio mais eficiente para a assimilação e acumulação de mercúrio na sua forma organometálica. 27,32 Os peixes assimilam o metilmercúrio principalmente através da ingestão do alimento, isto é, através da transferência trófica do MeHg da presa para predador. 20 Neste estudo, a transferência trófica do MeHg ao longo da cadeia trófica da Baía de Guanabara foi avaliada através da transferência do metilmercúrio, que estava acumulado nos tecidos das presas (organismos planctônicos e peixes planctívoros) para os predadores pouco vorazes (Micropogonias furnieri -corvina, Centropomus undecimalis -robalo, Orthopristis ruber -cocoroca) e destes para o predador de topo de cadeia (Trichiurus lepturus -peixe-espada).…”
Section: Metilmercúrio Na Biota Aquáticaunclassified
“…Desta forma, verificou-se que onde ocorreu o maior número de cianobactérias foi o local em que o microplâncton apresentou a maior Observando-se a Figura 1, verifica-se que FBC aumentou sucessivamente com o nível trófico da biota na cadeia alimentar, desde a base até o topo da cadeia alimentar aquática estudada, isto é, do microplâncton (produtor primário) para o mesoplâncton e mexilhão (consumidores primários), peixes planctívoros, peixes predadores pouco vorazes e peixe predador voraz. Esta observação suporta o fato de que o MeHg foi progressivamente acumulado ao longo da cadeia alimentar aquática, principalmente nos níveis mais altos 27,32 indicando, então, que esta forma orgânica de mercúrio pode estar sofrendo o processo de biomagnificação ao longo da cadeia alimentar da região estudada.…”
Section: Parâmetros Físicos E Químicos Nutrientes E Metilmercúrio Naunclassified
“…Par exemple, le transfert proie-prédateur plus efficace du MeHg et sa plus longue demi-vie biologique comparativement au mercure inorganique résultent en des concentrations de MeHg plus élevées chez les organismes de niveau trophique supérieur que chez ceux de niveau trophique inférieur (BROUARD ef al., 1994 ;FRANCESCONI et LENANTON, 1992 ;HILL étal., 1996 ;KIM et BURGGRAAF, 1999 ;MASON et al, 2000). Ce phénomène de biomagnification n'est pas observé pour les ions inorganiques des métaux (BRYAN et LANGSTON, 1992).…”
Section: -Introductionunclassified